'"For a better life …" A study on migration and health in Nicaragua'. Issue 1 (1st January 2018) - Gustafsson, Cecilia
ABSTRACT: Background : Nicaraguans have migrated internally and internationally for centuries due to economic, political and sociocultural factors. Deficiencies in the country's health care system have produced inequities in people's access to health care and medicines. Remittances have become an important source of income, partly invested in health. Objectives : The overall aim of the study was to analyse migration–health relations in contemporary Nicaragua within a broader context of socio-economic transformations. Methods : The study uses a mixed-methods approach, combining qualitative interview data and quantitative survey data. Results : The findings show that migration is commonly practised as a strategy for making a living and is related to the struggle for a better life. Health concerns are indirectly embedded in people's mobile livelihoods, but also directly influence migration motives. Furthermore, migration involves both advantages and disadvantages for health. Physical and sexual violence can come to an end for migrating women, health care and medicine can become more accessible for internal migrants, and vulnerabilities caused by environmental disasters can be avoided by moving. Moreover, remittances can improve people's everyday life and health. Yet migration can also be a stressful and health-damaging event. International migrants, particularly the undocumented, can have problems accessing health care, and also experience much danger at border crossings. Transnational families can suffer emotionally as well as physically due to separation. Findings from the survey show that family members of migrants do not rate their physical health as good as often as non-migrating families. Conclusions : The Nicaraguan population is not guaranteed its social rights of citizenship. This results in mobile livelihoods and the need for translocal social support (e.g. remittances). Migration can have both positive and negative effects on health for migrants and their family members; geographical distance and social differences are key to the outcome.